2005
DOI: 10.1111/j.1528-1167.2005.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

The Acute and Chronic Effect of Vagus Nerve Stimulation in Genetic Absence Epilepsy Rats from Strasbourg (GAERS)

Abstract: Summary:Purpose: The aim of this study was to evaluate the efficacy of acute and chronic vagus nerve stimulation (VNS) in genetic absence epilepsy rats from Strasbourg (GAERS). This is a validated model for absence epilepsy, characterized by frequent spontaneous absences concomitant with spike and wave discharges (SWD) on the EEG. Although absences are a benign form of seizures, it is conceptually important to investigate the efficacy of VNS in a controlled study by using this chronic epilepsy model.Methods: B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
10
1
1
Order By: Relevance
“…These values were improved at hours 22, 24 and 26. These data were different than those observed in previous studies (4,5). This difference may come from variations between the animal strains, per se.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…These values were improved at hours 22, 24 and 26. These data were different than those observed in previous studies (4,5). This difference may come from variations between the animal strains, per se.…”
Section: Resultscontrasting
confidence: 99%
“…There are some reports by Dedeurwaerdere et al who particularly studied the acute and chronic effects of VNS on GAERS rats, one of the two animal strains validated for absence seizures (4,5). In the article on acute effects of VNS; they could not show any effect of applying stimulation to vagal nerve on SWC whether performed at the onset or during the discharges.…”
Section: █ Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Statistical significance: *P <0.05. Table 2 The difference among the five cases in the number of spikes, the maximum amplitude of spikes, and the number of spike-positive electrodes in the VNS ON and OFF phases Neurologia medico-chirurgica Advance Publication Date: April 15, 2020 possibilities have been suggested, such as the change in the neurotransmitters' concentration, [22][23][24] expression of a new protein, 25,26) and change in the local brain blood flow. [27][28][29] Most of the previous studies demonstrated the VNS long-term effects using the trans-scalp EEG recording.…”
Section: Discussionmentioning
confidence: 99%
“…In our group, we have demonstrated the efficacy and safety of vagus nerve stimulation (VNS) and deep brain stimulation (DBS) in both patients and experimental animal models for epilepsy. [4][5][6][7][8] Other possible alternative treatments are newly developed AEDs, 9 the ketogenic diet 10,11 and transcranial magnetic stimulation. 12 In spite of all these developments, a significant number of patients continue to have uncontrolled seizures which makes a further search for alternative treatments mandatory.…”
Section: Introductionmentioning
confidence: 99%